Diagnostic Accuracy of Modified Biophysical Profile in Predicting Poor Perinatal Outcome in Pregnancies Complicated by Hypertension at Term - Rabia Awan, Natasha Bushra, Wajiha Rizwan, Attka Maryam, Uzma Zia, Shazia Haider, Tayyiba Wasim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypertension in pregnancy has an impact to improve the perinatal and maternal morbidity and mortality which is very important determinant to improve sustainable developmental goals. The high perinatal mortality in women with hypertension in pregnancy is mainly due to fetal growth restriction and iatrogenic preterm delivery. Aim: The diagnostic accuracy of modified biophysical profile is assessed in predicting perinatal outcome in hypertensive pregnancies taking Apgar score at 5 minutes at gold standard Methods: A cross sectional study was conducted in Department of Obstetrics & Gynecology, Unit II Services Hospital, Lahore from 26-6-2021 to 26-12-2021. After meeting the inclusion criteria 180 females were enrolled. Then all females underwent assessment of MBPP. All females were managed efficiently as per standard management protocols. Then females followed-up till delivery of baby. Data analysis was done on SPSS version 22. Results: In this study the mean age of the females was 30.27±5.91 years, there were 29(16.11%) females were nulliparous, 44(24.44%) females had parity 1. MBBP predict poor perinatal outcome in 42(23.3%) females. The sensitivity, specificity and diagnostic accuracy of MBPP was 72%, 95.38% & 88.89% respectively. Conclusion: This present study concluded that the modified biophysical profiles a useful and cost effective tool for predicting perinatal outcome in hypertensive pregnancies Keywords: Pregnancy, Perinatal outcome, Modified Biophysical Profile